Right to self -determination, and rights of indigenous people and minorities - Eishan Jan, Mohammad Naqib (s.n, 2012)
The right to self-determination and right of indigenous people and minorities are recognized in international human right law. This research attempts to define the term self-determination, establishes its origin, from, interpretation, constraints and limitations, and determines the question as to who is eligible to claim internal self-determination and who is eligible to claim external self-determination